2018
DOI: 10.1177/0885066618783656
|View full text |Cite
|
Sign up to set email alerts
|

Positive Culture and Prognosis in Patients With Sepsis: A Prospective Cohort Study

Abstract: Purpose: To analyze the prognostic role of positive cultures in patients with sepsis. Methods: A prospective cohort study in a tertiary referral hospital in Medellín, Colombia. Adults older than 18 years of age with a bacterial infection diagnosis according to Centers for Disease Control criteria and sepsis (evidence of organ dysfunction) were included. A logistic regression model was used to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The findings of Marco et al were similar to ours, and mortality did not increase with a positive test result for bacteraemia 25 . In another prospective cohort study, positive blood cultures were not associated with outcomes in patients with sepsis 31 . A recent meta-analysis also showed that positive or negative blood cultures were not associated with mortality in patients suffering fromsepsis 32 .…”
Section: Discussionmentioning
confidence: 93%
“…The findings of Marco et al were similar to ours, and mortality did not increase with a positive test result for bacteraemia 25 . In another prospective cohort study, positive blood cultures were not associated with outcomes in patients with sepsis 31 . A recent meta-analysis also showed that positive or negative blood cultures were not associated with mortality in patients suffering fromsepsis 32 .…”
Section: Discussionmentioning
confidence: 93%
“…( 29,30 ) Similarly, it has been described that patients with sepsis without focus and negative cultures have lower mortality than patients with positive cultures; ( 31 ) however, our findings, which we have corroborated in another recently published study, did not agree with this statement. ( 32 )…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the above understanding of the pathogenesis of sepsis, several treatment methods have been established for sepsis patients including antibiotics, hemodynamic management, infection source control, etc. ; however, their mortality risk remains high 8‐12 . Thus, it is helpful to explore potential biomarkers for sepsis, based on which clinicians could manage patients timely to improve their prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…; however, their mortality risk remains high. 8 , 9 , 10 , 11 , 12 Thus, it is helpful to explore potential biomarkers for sepsis, based on which clinicians could manage patients timely to improve their prognosis.…”
Section: Introductionmentioning
confidence: 99%